Organosoluble starch derivative as quasi-solid electrolytes in DSSC: Unravelling the synergy between electrolyte rheology and photovoltaic properties - Selvanathan V.; Yahya R.; Alharbi H.F.; Alharthi N.H.; Alharthi Y.S.; Ruslan M.H.; Amin N.; Akhtaruzzaman M. (Elsevier Ltd, 2023)
Adhesives; Biomechanics; Cellulose; Charge transfer; Efficiency; Elasticity; Electrochemical impedance spectroscopy; Gels; Polyelectrolytes; Potentiometric sensors; Rheology; Solid electrolytes; Starch; Adhesive properties; Charge transfer process; Electrode/electrolyte interfaces; Hydroxyethyl cellulose; Hydroxyethyl celluloses (HEC); Photovoltaic property; Polymer gel electrolytes; Rheological analysis; Dye-sensitized solar cells; cellulose; dye; electrolyte; fuel cell; organic compound; photovoltaic system; rheology; starch; Adhesives; Cellulose; Charge Transfer; Efficiency; Elasticity; Gels